Analysis of Ownership Structure Effect on Economic Value Added - Henryani, Friska Fardhina; Kusumastuti, Retno (BISNIS & BIROKRASI: Jurnal Ilmu Administrasi dan Organisasi, 2014)
Ownership structure has a direct relationship with company’s capital structure where the cost of capital is the main component in the calculation of economic value added to measure the value of the firm. This research aims to analyze the effect of ownership structure that consists of managerial ownership, public ownership, institutional ownership, and government ownership on economic value added, used as a measurement of the firm value. This research uses an unbalanced panel data of 182 observations data of all listed companies in the period of 2007-2011 that issued dividend regularly every year during the research’s year. The result shows: (1) managerial ownership has no significant effect on economic value added, (2) public ownership has a significant positive effect on economic value added, (3) institutional ownership has a significant positive effect on economic value added, (4) government ownership has no significant effect on economic value added, (5) ownership structure (managerial ownership, public ownership, institutional ownership, government ownership) simultaneously has a significant positive effect on economic value added.